Spectrophotometric Determination of Nitrofurantoin Drug in its Pharmaceutical Formulations Using MBTH as a Coupling Reagent - Hind Hadi; Marwa Mouayed (College of Pharmacy University of Baghdad, 2017)
A direct, sensitive and efficient spectrophotometric method for the determination of nitrofurantoin drug (NIT) in pure as well as in dosage form (capsules) was described. The suggested method was based on reduction NIT drug using Zn/HCl and then coupling with 3-methyl-2-benzothiazolinone hydrazone hydrochloride (MBTH) in the presence of ammonium ceric sulfate. Spectrophotometric measurement was established by recording the absorbance of the green colored product at 610 nm. Using the optimized reaction conditions, beer’s law was obeyed in the range of 0.5-30 μg/mL, with good correlation coefficient of 0.9998 and limits of detection and quantitation of 0.163 and 0.544 μg/mL, respectively. The accuracy and precision of the proposed method represented by recovery and relative standard deviation were satisfactory; about 99.33% and 1.16%, respectively. The proposed method was applied for determination of NIT in its pharmaceutical forms and the results compared successfully with those obtained by standard method (British pharmacopeia method). Keywords: Nitrofurantoin , MBTH , Oxidative coupling reaction.